Metabolic heterogeneity and plasticity of glioma stem cells in a mouse glioblastoma model. Issue 3 (2nd September 2017) - Shibao, Shunsuke; Minami, Noriaki; Koike, Naoyoshi; Fukui, Nobuyuki; Yoshida, Kazunari; Saya, Hideyuki; Sampetrean, Oltea
Abstract: Background: Glioblastomas have been shown to rely on glycolysis as an energy source. However, recent evidence suggests that at least a subset of glioma cells with stem cell–like properties can thrive on oxidative phosphorylation. It remains unclear whether both metabolic phenotypes support tumor propagation, if they are independent, and how stable they are. The present study investigated these questions with the use of isogenic murine glioma stem cells (GSCs). Methods: GSCs were established from tumors formed by Ink4a/Arf –null, H-Ras V12 -expressing glioma-initiating cells that differed in extracellular acidification potential. Metabolic characteristics of GSCs were determined by measurement of glucose, oxygen, and glutamine uptake, ATP content, and lactate production. Effects of metabolic inhibitors and changes in oxygen or nutrient availability on lactate production and tumorsphere growth were also determined. Results: GSCs were found either to consume more glucose and produce more lactate or to consume more oxygen and maintain a higher ATP content depending on the metabolic characteristics of the tumor cells of origin. The latter, mitochondrial-type GSCs increased lactate production after treatment with the oxidative phosphorylation inhibitor oligomycin or phenformin. Exposure to hypoxia also increased lactate production and expression of glycolysis-related enzymes and metabolites in mitochondrial-type GSCs in a reversible manner. Conclusions: Both glycolytic and mitochondrial-type energy production can sustain tumor propagation by isogenic GSCs. Whereas both phenotypes can be independent and stable, cells that rely on oxidative phosphorylation can also switch to a more glycolytic phenotype in response to metabolic stress, suggesting that plasticity is a further characteristic of GSC metabolism.